Interfacility Transport of the Pregnant Patient: A 5-year Retrospective Review of a Single Critical Care Transport Program. (4th May 2019) - Nawrocki, Philip S.; Levy, Matthew; Tang, Nelson; Trautman, Shawn; Margolis, Asa
Abstract: Introduction: Interfacility transport of the pregnant patient poses a challenge for prehospital providers as it is an infrequent but potentially high acuity encounter. Knowledge of clinically significant events (CSEs) that occur during these transports is important both to optimize patient safety and also to help enhance crew training and preparedness. This study evaluated a critical care transport program's 5-year longitudinal experience transporting pregnant patients by ground and air, and described CSEs that occurred during the out-of-hospital phase of care. Methods: This study was a retrospective review of pregnant patients transported by a single critical care transport system into and within a large academic healthcare system. Patients who were pregnant, and were transported from a referring facility to one of the 2 receiving centers within Johns Hopkins Health System between January 1, 2012 and December 31, 2016 were included in this study. The primary outcome of interest was the occurrence of a predefined clinically significant event (CSE) during transport, while a secondary outcome of interest was the indication for transfer. Results: During the study period 1, 223 pregnant patients were transported by our critical care transport service. There were 1, 101 patients who met inclusion criteria; 693 (62.9%) of whom were transported by ground and 408 (37.1%) who were transported by rotor wing aircraft. The top 3 indications for transfer comprised 71.4% of all patients and included; preterm labor, hypertensive disorder of pregnancy, and other maternal life threatening disorder. The most common events that occurred across all transports were: exacerbation of hypertensive disease requiring intervention (4.5%), hypotension (1.3%), and altered mental status (0.2%). Conclusions: Incidence of CSEs during the interfacility transport of pregnant patients within our critical care transport system is low (6.0%). Knowledge of the clinically significant events that occur during EMS transport is a vital component of ensuring system quality and optimizing patient safety. This data can be used to augment and focus provider education and training to mitigate and optimize response to future events.